2020
DOI: 10.1155/2020/2198960
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Biomarker-Guided Treatment for Metastatic Gastric Cancer in the Second-Line Setting

Abstract: Background. e 5-year survival rate of patients with metastatic gastric cancer (GC) is only 5%. However, trials have demonstrated promising antitumor activity for targeted therapies/immunotherapies among chemorefractory metastatic GC patients. Pembrolizumab has shown particular efficacy among patients with programmed death ligand-1 (PD-L1) expression and high microsatellite instability (MSI-H). e aim of this study was to assess the effectiveness and cost-effectiveness of biomarker-guided second-line GC treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…One cost-effectiveness analysis on the topic of this guideline found that second-line treatment with targeted therapy or immunotherapy for patients with metastatic gastric cancer improved survival and quality-adjusted life years; however, costs were prohibitively expensive at a quality-adjusted lifeyear threshold of $100,000 in US dollars while single-agent paclitaxel was cost-effective at this threshold. 52 Of note, medication prices may vary markedly, depending on negotiated discounts and rebates. Patient out-of-pocket costs may vary depending on insurance coverage.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…One cost-effectiveness analysis on the topic of this guideline found that second-line treatment with targeted therapy or immunotherapy for patients with metastatic gastric cancer improved survival and quality-adjusted life years; however, costs were prohibitively expensive at a quality-adjusted lifeyear threshold of $100,000 in US dollars while single-agent paclitaxel was cost-effective at this threshold. 52 Of note, medication prices may vary markedly, depending on negotiated discounts and rebates. Patient out-of-pocket costs may vary depending on insurance coverage.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…The heavy burden of GC remains a problem particularly in Asia, with studies indicating a five-year survival rate for only 5% of patients with GC [ 2 , 20 ]. More recently, novel immunological therapies have been considered crucial tools capable of treating patients with GC at different stages in addition to more traditional therapies such as surgery, radiotherapy, chemotherapy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether such investment is warranted for the given risk-benefit profile is up to the individual regulatory and reimbursement agencies to decide, but analyses such as ours will be helpful for countries in priority setting in making such decisions. Cost-effectiveness analyses of ramucirumab also consistently reveal that ramucirumab is not cost-effective in various tumor types [ 26 , 27 ], including in the only biomarker-based approval of ramucirumab in hepatocellular cancer [28] . Indeed, ramucirumab has also been previously proposed as one of the low-value therapeutics in oncology with regards to its indication for gastric or gastroesophageal junction tumors [29] .…”
Section: Discussionmentioning
confidence: 99%